Changes in the game characteristics of a badminton match: A longitudinal study through the Olympic Game finals analysis in men´s singles - Laffaye, G.; Phomsoupha, M.; Dor, F. (Journal of Sports Science & Medicine, 2015)
The goal of this study was to analyze, through a longitudinal study, the Olympic Badminton Men`s singles finals from the Barcelona Games (1992) to the London Games (2012) to assess some changes of the Badminton game characteristics. Six Olympic finals have been analyzed based on the official video of the Olympic Games (OG) through the temporal structure and with a notational approach. In total, 537 rallies and 5537 strokes have been analyzed. The results show a change in the game`s temporal structure: a significant difference in the rally time, rest time and number of shots per rally (all p<0.0001; 0.09 < .² < 0.16). Moreover, the shot frequency shows a 34.0% increase (p<0.000001; .² = 0.17), whereas the work density revealed a 58.2% decrease (from 78% to 30.8%) as well as the effective playing time (-34.5% from 34.7±1.4% to 22.7±1.4%). This argues for an increase in the intensity of the game and a necessi-ty for the player to use a longer resting time to recover. Lastly, the strokes distribution and the percentage of unforced and forced mistakes did not show any differences throughout the OG analysis, except for the use of the clear. This results impact on the way the training of Badminton players should be designed, especially in the temporal structure and intensity.